2014
DOI: 10.4103/0974-2077.138352
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma in androgenic alopecia: Myth or an effective tool

Abstract: Platelet-rich plasma (PRP) has become a newer method for the treatment of various types of alopecia. In this prospective study, safety, efficacy and feasibility of PRP injections in treating androgenic alopecia were assessed. Eleven patients suffering from hair loss due to androgenic alopecia and not responding to 6 months treatment with minoxidil and finasteride were included in this study. The hair pull test was performed before every treatment session. A total volume of 2-3 cc PRP was injected in the scalp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(147 citation statements)
references
References 11 publications
2
134
1
4
Order By: Relevance
“…The positive effect of PRP in the treatment of AGA has been documented in other studies. [11,12,13].Mechanisms of hair regrowth induced by skin needling include: [14,15,16] release of platelet derived growth factor, epidermal growth factors through platelet activation and skin wound regeneration mechanism; activation of stem cells in the hair bulge area; overexpression of hair growth related genes vascular endothelial growth factor, B catenin, Wnt3a, and Wnt10 b. A 12-week study by Dhurat et al [17] showed that dermaroller along with Minoxidil treated group was statistically superior to Minoxidil treated group in promoting hair growth in men with AGA.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of PRP in the treatment of AGA has been documented in other studies. [11,12,13].Mechanisms of hair regrowth induced by skin needling include: [14,15,16] release of platelet derived growth factor, epidermal growth factors through platelet activation and skin wound regeneration mechanism; activation of stem cells in the hair bulge area; overexpression of hair growth related genes vascular endothelial growth factor, B catenin, Wnt3a, and Wnt10 b. A 12-week study by Dhurat et al [17] showed that dermaroller along with Minoxidil treated group was statistically superior to Minoxidil treated group in promoting hair growth in men with AGA.…”
Section: Discussionmentioning
confidence: 99%
“…These studies include Anitua et al [29], Puig et al [30], Mapar et al [31], Gupta et al [32], and Alves and Grimalt [33]. Studies from 2015 (Singhal et al [12] and Gentile et al [34]), 2014 (Gkini et al [27], Khatu et al [35], Schiavone et al [36], and Cervelli et al [28]), and 2011 (Takikawa et al [37]) are also compared. …”
Section: Methodsmentioning
confidence: 99%
“…Significant reduction in hair loss was evident per patient questionnaires. Both Gkini et al [27] and Khatu et al [35] assessed patient satisfaction, and found the reported means of 7.1 and 7.0 out of 10, respectively. …”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Basic fibroblast growth factor promotes the proliferation of papilla cells in vitro and, therefore, plays a key role in hair shaft elongation. Activated PRP promotes the proliferation and prevents apoptosis of dermal papillary cells [19].…”
Section: Androgenetic Alopecia (Aga)mentioning
confidence: 99%